Juggling Grandchild Care and Labor Force Participation: The Effect on Psychological Wellbeing of Older Women - Arpino, Bruno; Bellani, Daniela (Frontiers in Sociology, 2022)
Although it is well-known that care responsibilities are strongly gendered also in later life, the consequences for older women of juggling work and care responsibilities are understudied. This study contributes to fill this gap by focusing on the wellbeing implications for older European women of combining work and grandchild care. The role strain and role enhancement theories guide our theoretical predictions. While the former predicts a lower wellbeing due to the double burden of grandchild care and paid work, the latter posits an increase in wellbeing through the accumulation of social identities or roles. By using longitudinal data from the Survey of Health, Ageing and Retirement in Europe (SHARE), we investigate whether grandmothers who do and those who do not work experience different levels of quality of life, depressive symptoms and life satisfaction. Our statistical model consists in a fixed-effect regression that adjusts for the lagged outcome. Results show that, among grandmothers engaged in paid work, grandchild care is not significantly associated with any of the three outcomes considered. Instead, non-working grandmothers seem to benefit from provision of grandchild care, in terms of higher quality of life and lower number of depressive symptoms. As thus, the provision of grandchild care tends to be beneficial for grandmothers’ wellbeing only if they do not combine this activity with paid work. Juggling paid work and childcare to grandchildren may result in an excessive burden which eliminates the potential benefits of grandchild care on older women’s wellbeing.